2014
DOI: 10.1037/a0033819
|View full text |Cite
|
Sign up to set email alerts
|

A transactional analysis of the relation between maternal sensitivity and child vagal regulation.

Abstract: A transactional model examining the longitudinal association between vagal regulation (as indexed by vagal withdrawal) and maternal sensitivity from age 2.5 to age 5.5 was assessed. The sample included 356 children (171 male, 185 female) and their mothers who participated in the 2.5, 4.5, and 5.5 year laboratory visits. Cardiac vagal tone was obtained during a baseline task and during emotional frustration tasks. Maternal sensitivity was assessed via direct observation during a pretend play and cleanup task. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 79 publications
3
59
0
1
Order By: Relevance
“…Adoptive parents’ perceptions of their adopted child’s anger, measured before parenting observations, support the importance of considering reciprocal effects in studies of parenting (Bell, 1968; Brody & Ge, 2001; Lengua, 2006; Perry et al, 2014, 2017; Shaw & Bell, 1993). That is, children who display more anger may be at greater risk of eliciting negative parenting behaviors, particularly from their mothers, a finding that is consistent with similar work in this area (e.g., Larsson et al, 2008; Marceau et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Adoptive parents’ perceptions of their adopted child’s anger, measured before parenting observations, support the importance of considering reciprocal effects in studies of parenting (Bell, 1968; Brody & Ge, 2001; Lengua, 2006; Perry et al, 2014, 2017; Shaw & Bell, 1993). That is, children who display more anger may be at greater risk of eliciting negative parenting behaviors, particularly from their mothers, a finding that is consistent with similar work in this area (e.g., Larsson et al, 2008; Marceau et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Parenting, including maltreatment, also has demonstrated relations with children’s emotional SR (e.g., Cole, Dennis, Smith-Simon, & Cohen, 2009; Lilly, London, & Bridgett, 2014; Roth & Assor, 2012), including vagal withdrawal and RSA (e.g., Perry, Mackler, Calkins, & Keane, 2014; Skowron et al, 2011). Evidence also is accumulating that shows relations linking caregiving with the structural/functional development of neural areas essential for children’s top-down and bottom-up SR (See Belsky & de Haan, 2011 for a review).…”
Section: Associations Between Parent and Child Self-regulationmentioning
confidence: 99%
“…For example, researchers have found affective and autonomic synchrony to be present in parent–infant interactions (for a review, see Feldman, 2012), and bidirectional longitudinal relations between children’s physiological regulation and maternal sensitivity across early childhood (Perry, Mackler, Calkins, & Keane, 2014). Hastings and colleagues (2008) also reported that mothers who used more negative control had children with lower levels of RSA.…”
Section: Antecedents To Children’s Sympathymentioning
confidence: 99%